Study of the thermal drifts on the piezoresistivity using mobility model and finite difference method of electric heater - Abdelaziz Beddiaf; Fouad Kerrour (Bulletin of Electrical Engineering and Informatics, 2023)
In pressure sensors, four piezoresistors connected in a Wheatstone bridge are often provided with a voltage varying between 5 and 10 V. Unfortunately, this voltage is a source of drifts created by electric heating. This study focuses on the internal heating and piezoresistive effect of piezoresistors represented by the variation of their resistivity. To do this, we use the finite difference method (FDM) to solve the heat transfer equation, taking into account the conduction in Cartesian coordinates for the variable regime. We examine how the temperature affects the piezoresistivity in these sensors when the potential is applied. In this case, the variation of the temperature has been calculated as a function of applied voltage, as well as for the operating time of the sensor. Furthermore, the evolution of resistivity over time was determined for several geometric properties of the membrane using the mobility model. This was established for different doping levels. Additionally, the change in resistivity due to the application of voltage was evaluated. It was observed that resistivity is greatly affected by the temperature rise produced by the applied voltage when the device is actuated for a prolonged time. Consequently, this results in drifting in the output response of the sensor.